Demonstration and Audio-Visual Methods for Improving Knowledge, Attitude and Skills of Breast Care among Pregnant Women - Wirda Hayati; Dewi Marianthi; Nurhayati Nurhayati; Tantut Susanto (Faculty of Nursing Universitas Padjadjaran, 2020)
One of the physical changes during pregnancy is their breasts that usually get larger and heavier, the areola mammae becomes darker and the nipples get bigger. These conditions cause the breasts need to be treated in preparation for exclusive breastfeeding. However, in reality, there are many pregnant women who have not done much breast care due to their ignorance of its importance and lack of information. The aimed this study was to identify the effective of audio-visual and demonstration method for improving knowledge, attitude, and skills of breast care among pregnant women in Aceh. This study was used a pre-test post-test design with a control group (37 of pregnant women) and intervention group (36 of pregnant women). The intervention group was given health education about breast care using demonstration method, while the control group was given by watching videos. The instruments used in this study was a questionnaire about breast care and checklist to assess breast care skill. The instruments was developed based on the existing theory. Data was analyzed using t-independent test (p<0.05). There were significantly difference of knowledge (72.83 + 8.48 vs. 45.43 +12.06), attitudes (58.76 +6.20 vs. 46.83 + 4.58), and skill (73.74 + 7.98 vs. 56.17+ 10.62) of breast care between intervention and control group among pregnants women (P<0.001). Furthermore, the scores of knowledge, attitudes, and skills of breast care among pregnant women using demonstration (intervention groups) method were more higher compared pregnant women using audio-visual method (control groups). Health education using demonstration method is more effective for improving knowledge, attitudes, and skills of breast care among pregnant women than audio visual method. Therefore, demonstrations and re-demonstration using guideline should be implement for women with guidance during pregnant.